Pemanfaatan media sosial bagi pengembangan umkm di desa kedungrejo, kecamatan jabon, sidoarjo - Istanti, Enny; Sanusi, Ruchan (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2020)
Social media is a tool or means that can be accessed by everyone without limitation of time and distance as long as there is an internet network. The existence of social media that has wide, easy, and fast access is used by MSME small entrepreneurs to be more courageous in promoting their products as an effective and efficient marketing medium. The rapid development of MSMEs has made the use of social media even higher. The existence of MSMEs is expected to be able to expand employment opportunities, accelerate the process of economic equality, increase community income, and promote national stability. The use of social media is expected to be able to increase the marketing reach of MSME businesses. With the Thematic Real Work Lecture program, it is hoped that outreach and training activities on the development of MSME marketing in Kedungrejo Village through social media can provide an understanding of the importance of social media in developing business while keeping up with the times and can be used as much as possible.Â Keywords:Â UMKM; Social media; Extension; Training.